2018
DOI: 10.1080/1360144x.2018.1545233
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing outcomes and reducing inhibitors to the engagement of students and staff in learning and teaching partnerships: implications for academic development

Abstract: and Marquis, Elizabeth (2019) Enhancing outcomes and reducing inhibitors to the engagement of students and staff in learning and teaching partnerships: implications for academic development. International Journal for Academic Development, 24 (3). pp. 246-259.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…When students and faculty bring their respective perspectives to the partnership (Cook-Sather, Bovill, and Felten 2014; Mercer-Mapstone and Marie 2019), the expected result is that each party can learn from the other, with the ultimate impact being that the symbiotic partnership, as a whole, is able to achieve teaching and learning practices beyond that of the sum of its parts (Coombe et al 2018). Common benefits to students include enhanced motivation, stronger sense of belonging, and deepened understanding of pedagogical practices (Barrineau et al 2016;Goff and Knorr 2018;Matthews et al 2018;Peets et al 2009). Faculty members and academic developers benefit from incorporating student perspectives from authentic student sources into pedagogical practices (Cook-Sather et al 2017;Kligyte et al 2019;Marquis et al 2016).…”
Section: Benefits Of Students As Partnersmentioning
confidence: 99%
See 1 more Smart Citation
“…When students and faculty bring their respective perspectives to the partnership (Cook-Sather, Bovill, and Felten 2014; Mercer-Mapstone and Marie 2019), the expected result is that each party can learn from the other, with the ultimate impact being that the symbiotic partnership, as a whole, is able to achieve teaching and learning practices beyond that of the sum of its parts (Coombe et al 2018). Common benefits to students include enhanced motivation, stronger sense of belonging, and deepened understanding of pedagogical practices (Barrineau et al 2016;Goff and Knorr 2018;Matthews et al 2018;Peets et al 2009). Faculty members and academic developers benefit from incorporating student perspectives from authentic student sources into pedagogical practices (Cook-Sather et al 2017;Kligyte et al 2019;Marquis et al 2016).…”
Section: Benefits Of Students As Partnersmentioning
confidence: 99%
“…Even in non-western contexts, the student-faculty partnership positively contributes to student engagement, development, and academic functioning (Kaur, Awang-Hashim, and Kaur 2019). Overall, student-faculty partnerships have the potential to achieve shared respect and trust, more inclusive educational practices (Matthews et al 2018), and enriched learning from one another within collaborative learning communities (Lubicz-Nawrocka 2018).…”
Section: Benefits Of Students As Partnersmentioning
confidence: 99%
“…A systematic literature review of SaP studies found over 60 empirical publications between 2010-2015 in English language outlets mainly from a handful of countries (USA, UK, Canada, Australia and some western European countries) that documented a range of beneficial outcomes for both students and staff involved in SaP practices (Matthews et al, 2019b;Mercer-Mapstone et al, 2017). Analysis of theoretical frames in research on SaP found that the constructs of power and identity underpinned partnership practices as relational praxis that calls into question taken-for-granted assumptions about the role of the teachers and the students in ways that illuminate power dynamics and relational identities by giving permission to learners and teachers to reshape them (Matthews et al, 2019a).…”
mentioning
confidence: 99%
“…In the context of SaP, Cook-Sather (2015, p. 2) defined the notion of identity as 'how individuals define and experience themselves and are defined by others-how an individual/personal sense of sociocultural location and character intersects with how that individual is constructed in many different ways within any given culture and society' . Therefore, identity in partnership is about how teachers and students treat themselves as teacher, student, and partners, and how they perceive each other (Matthews et al, 2019b). As one of the important factors of pedagogical partnership, Cook-Sather (2015) pointed out that the identities of students and teachers influence and are influenced by partnership.…”
mentioning
confidence: 99%
See 1 more Smart Citation